Analisis Bibliometrik Menggunakan Model Problem Based Learning (PBL) terhadap Pemecahan Masalah Matematis - Qori’ah Febri Yanti; Hasanuddin Hasanuddin (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Mathematics learning does not only focus on students' mastery of numbers, but also functions significantly in developing the ability to solve problems holistically. This skill is not something that is taught separately, but is integrated into the entire educational process, offering a real context so that mathematical concepts and abilities can be understood and applied. One approach that is highly recommended to achieve this is Problem Based Learning (PBL). This method has been proven effective in improving students' critical thinking skills through exploration and solving relevant problems, allowing students' knowledge to grow in a constructive way. The low achievement in problem-solving competency in Indonesia is a strong reason to apply PBL in mathematics teaching. This study aims to analyze the literature on the application of PBL to improve students' problem-solving abilities. Data were collected and analyzed from relevant journals, and testing and comparison of results were carried out to identify patterns and results from previous studies. In addition, this study also applies a bibliometric approach to explore publication trends, keywords, and the development of themes related to PBL in mathematics education. The analysis was carried out using VOSviewer software to map the relationship between topics and the progress of PBL research themes in the world of mathematics education.